Moderate Versus High Intensity Interval Exercise Training Reduce the Clinical Components of Metabolic Syndrome in Previously Physically Inactive Adults: A Randomized Clinical Trial - Garcia-Hermoso, A (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Sin Resumen Disponible